The Effect of Digital Communication Load on The Mental Health of Gen Z Employees in Educational Institutions With Fear of Missing Out as A Mediation Variable - Muchamad Ramdani; Rita Destiwati (Eduvest - Journal of Universal Studies, 2025)
The transformation of organizational communication from conventional forms to digital platforms has reshaped the way individuals interact within the workplace. While the acceleration of information flow through digital media enhances efficiency, it also introduces new psychological pressures, particularly for Generation Z employees who are highly connected online. This study aims to examine the effect of digital communication overload on the mental health of Generation Z employees in educational institutions, with Fear of Missing Out (FoMO) serving as a mediating variable. Employing a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), the research draws upon data from 253 respondents—consisting of lecturers and academic support staff aged 22 to 28 years—at Telkom University in Bandung. The findings reveal that digital communication overload has a significant effect on mental health (β = 1.033; t = 111.882; p = 0.000) and significantly increases FoMO (β = 0.973; t = 272.540; p = 0.000). FoMO exerts a negative effect on mental health (β = −0.034; t = 3.581; p = 0.000) and acts as a significant mediator in the relationship between digital communication overload and mental health (β_ind = −0.033; t = 3.586; p = 0.000). This study underscores the urgency of implementing adaptive digital communication policies that are grounded in psychological well-being, particularly for young professionals in academic settings.